Cambodia agriculture, natural resources, and rural development sector assessment, strategy, and road map. (Asian Development Bank, 2021)
It identifies the strategic investment priorities of the Government of Cambodia where the Asian Development Bank (ADB) can contribute to ANRRD productivity, value addition, and resource efficiency. ADB support will focus on three key areas: (i) enhancing agricultural productivity through a whole of system water resources management approach, (ii) strengthening agricultural value chains, and (iii) improving natural resources management and disaster resilience.